Penataan Kawasan Wisata Lakkang Berbasis Masyarakat - Ihsan Latief; Abdul Rachman Rasyid (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Tourism in Indonesia consists of various types of tourist objects which until now have become the main attraction for both domestic and foreign tourists. A tourist area needs its own arrangement so that tourists can be interested in visiting that location. The arrangement of a strategic and attractive area to become a tourist destination has been found in many regions. Most of these locations are arranged based on the wishes and expectations of the people who live in the area. The importance of the role of local communities in the development of sustainable tourism destinations has encouraged the emergence of new trends in community-based tourism development. This is also done in the area of ​​Lakkang Village, which is one of the locations that has tourism potential in Makassar City. This research aims to explain the arrangement of the Lakkang area into a tourist area based on a community perspective. Data collection techniques are carried out by observing the existing area, reviewing data or documents related to the area and interviews conducted in Focus Group Discussion (FGD) activities with the community in the Lakkang delta area. The analysis technique of this research uses descriptive qualitative and spatial analysis. The results of this study indicate the existing tourism potential in the Lakkang delta, as well as the use of the ecotourism concept as a concept that can benefit not only the community but also the preservation of the tourist area in Lakkang village.